How to reduce the exposure risk of medical staff from SARS-CoV-2 by reducing environmental contamination: Experience from designated hospitals in China - Zeng, Cui; Liu, Hengzhuo; Jiang, Yuling; Fu, Yuanyu; Liu, Yuan; Chang, Wei; Li, Tingting; Huang, Xun; Li, Chunhui (Frontiers in Public Health, 2022)
Background Using daily monitoring of environmental surfaces and personal protective equipment (PPE), we found an increase in environmental contamination since August 18, 2021, in a designated hospital for COVID-19 patients in China, which may lead to an increased risk of exposure to medical staff. Methods To investigate the cause of increased environmental contamination and effect of our intervention, we obtained environmental samples at pre-intervention (August 18–21, 2021) and post-intervention (August 22–28, 2021) from six infection isolation rooms with windows for ventilation and other auxiliary areas at 105 and 129 sites before routine daily cleaning, respectively. In addition, we obtained PPE samples from 98 medical staff exiting the patient rooms/contaminated areas at 482 sites. Between August 22 and 24, 2021, we took measures to reduce environmental contamination based on sampling and inspection results. Findings At pre-intervention, the positivity rates for contamination of environmental surfaces and PPE samples were significantly higher for critical patients (37.21 and 27.86%, respectively) than severely ill patients (25.00 and 12.50%, respectively) and moderately ill patients (0.00 and 0.00%, respectively) (Pearson's Chi-square: χ2 = 15.560, p = 0.000; Fisher's exact test: χ2 = 9.358, p = 0.007). Therefore, we inferred that the source of contamination of environmental surfaces and PPE was mainly the room of critically ill patients, likely through the hands of medical staff to the potentially contaminated areas. A critically ill patient had emergency tracheal intubation and rescue on August 18, 2021, due to worsened patient condition. The ventilator tube used for first aid did not match the ventilator, and the ventilator tube fell off multiple times on August 18–21, 2021, which may explain the increased contamination of environmental surfaces and PPE from critically ill patients, as well as lead to indirect contamination of potentially contaminated areas. The contamination positivity rates of environmental surfaces and PPE were reduced by replacing the appropriate ventilator catheter, limiting the number of people entering the isolation room simultaneously, increasing the frequency of environmental disinfection, standardizing the undressing process, setting up undressing monitoring posts to supervise the undressing process, and preventing the spread of virus infections in the hospital during an epidemic. Conclusions Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was spread on object surfaces in isolation rooms mainly by touch, and the contamination of environmental surfaces and PPE was greater in rooms of patients with greater disease severity and higher surface touch frequency. Therefore, strict protective measures for medical staff, frequent environmental cleaning for isolation rooms, and compliance with mask wearing by patients when conditions permit should be advised to prevent SARS-CoV-2 spread in hospitals.